2017
DOI: 10.3233/fi-2017-1500
|View full text |Cite
|
Sign up to set email alerts
|

Non-differentiable Solutions for Local Fractional Nonlinear Riccati Differential Equations

Abstract: Abstract. We investigate local fractional nonlinear Riccati differential equations (LFNRDE) by transforming them into local fractional linear ordinary differential equations. The case of LFNRDE with constant coefficients is considered and non-differentiable solutions for special cases obtained.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…We obtain the family of the nonlinear local fractional ordinary differential equations as follows. Family A When = 1, we have the following nonlinear local fractional ordinary differential equation 23,24 d Ω ( )…”
Section: Some Exact Solutions For the Nonlinear Fractal Burgers' Equamentioning
confidence: 99%
“…We obtain the family of the nonlinear local fractional ordinary differential equations as follows. Family A When = 1, we have the following nonlinear local fractional ordinary differential equation 23,24 d Ω ( )…”
Section: Some Exact Solutions For the Nonlinear Fractal Burgers' Equamentioning
confidence: 99%
“…The local fractional derivative is discussed as βv(),ξηηβ=Δβ(),v(),ξηvtrue(ξη0true)ηη0, where Δβ(),v(),ξηvtrue(ξη0true)normalΓ()1+β[],v(),ξηvtrue(ξη0true). …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Many researchers worked to model wave equations from the well-known wave equations by substituting the standard derivatives by the arbitrary order derivative. 5,6 Nowadays, the local fractional calculus 7 is tried to report the nondifferentiable problems, for example, heat conduction problem involving local derivative of fractional order, 7,8 local fractional Tricomi equation, 9 fractal vehicular traffic flow, 10 Laplace equation containing local fractional operator, 11 nonlinear gas dynamics equation, and coupled KdV equation pertaining to local operator of noninteger order, 12 the wave equation involving noninteger order derivative introduced by Yang, 13 the system of partial differential equations with local operator of noninteger order, 14 heat conduction equations with local fractional calculus, 15 nonlinear Riccati differential equations involving local fractional operator, 16 local fractional telegraph equations occurring in electrical transmission line, 17 local fractional LWR equation, 18 local fractional modeling in growths of populations, 19 local fractional model is used in kidney images enhancement, 20 Fitzhugh-Nagumo equations with local fractional derivative, 21 mathematical model of shallow water waves with the aid of local fractional KdV equation, 22 Boussinesq equation containing local fractional operator, 23 local fractional KdV equation, and its exact traveling wave solution, 24 etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractional calculus has a 300-year-old history, however its applications in physics and engineering were only recently identified. Some very recent papers on its applications are given in [13,16,18,22,26,30,38,39] and the references therein. It was found that many systems in interdisciplinary fields can be elegantly described with the help of fractional derivative such as given in [22] and [30].…”
Section: Introductionmentioning
confidence: 99%